2002
DOI: 10.1002/syn.10168
|View full text |Cite
|
Sign up to set email alerts
|

Fimbrial control of bidirectional synaptic plasticity of medial perforant path‐dentate transmission

Abstract: Lesions of the fimbria-fornix (FF) tract cause profound impairments of cognitive ability in animals. Our previous study showed that spatial performance correlates with long-term potentiation (LTP) of the dentate gyrus (DG), but not of the CA1 region, in rats with bilateral FF lesions, suggesting that FF lesions selectively inhibited LTP in the DG. The cortical input to the DG is anatomically and physiologically divided into two types of afferents, i.e., the medial perforant path (MPP) and the lateral perforant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Based on lesions of the fimbria-fornix, Jas et al (2000) suggested that two independent DG-LTP modulatory pathways within the BLA-hippocampus system may exist (cf. Nakao et al, 2003), and Akirav and Richter-Levin (2002) found a ␤-adrenergic dependence on DG-LTP modulation by stimulating the ipsilateral but not the contralateral BLA, which also points to independent modulatory inputs.…”
Section: Discussionmentioning
confidence: 90%
“…Based on lesions of the fimbria-fornix, Jas et al (2000) suggested that two independent DG-LTP modulatory pathways within the BLA-hippocampus system may exist (cf. Nakao et al, 2003), and Akirav and Richter-Levin (2002) found a ␤-adrenergic dependence on DG-LTP modulation by stimulating the ipsilateral but not the contralateral BLA, which also points to independent modulatory inputs.…”
Section: Discussionmentioning
confidence: 90%
“…By combining complex spike activity with theta rhythm, TBS approximates naturally occurring patterns of cell firing observed in the hippocampus and has been associated with widespread effects on synaptic efficiency and dynamic oscillation patterns (Diamond, ). Application of TBS to hippocampal afferent pathways produces robust and sustained long‐term potentiation (LTP) that is most effective in the theta range (i.e., 5 Hz, or 200 ms between pulses) (Nakao, ). LTP represents a long‐lasting increase in synaptic efficiency triggered by repetitive stimulation that produces postsynaptic Ca 2 + influx through N ‐methyl‐D‐aspartic acid (NMDA) glutamate receptors and, under some conditions, L‐type voltage‐gated Ca 2 + channels (Collingridge, ; Grover, ).…”
Section: Discussionmentioning
confidence: 99%
“…Other mechanisms may include dysregulated cellular homeostasis within the hippocampus (D'Ambrosio, ), dysfunctional synaptic neurotransmission (Toth, ; D'Ambrosio, ), regional changes in circuit excitability (Witgen, ), and a decrease in intrinsic hippocampal theta oscillations (Fedor, ). Disruption of the theta rhythm and synaptic function are particularly important because both have been implicated in the pathophysiology of memory loss (Winson, ; Nakao, ).…”
Section: Introductionmentioning
confidence: 99%
“…2 A (20,21). By changing the number of stimuli in each burst train, we find that LFBS, when delivered to the MPP, can produce varying levels of synaptic plasticity, i.e., a continuum from LTP to LTD, without any priming stimulation (Fig.…”
mentioning
confidence: 89%